"All we have to do, is do it all": Exploring middle-career women's academic identities in Australian higher education using Foucauldian Discourse Analysis. (January 2023) - Phillips, Matthew J.; Dzidic, Peta L.; Roberts, Lynne D.; Castell, Emily L.
Abstract: We explored how middle-career women academics within Australian public higher education conceptualise their academic identities, and the subject positions made available through later-career women's discourse. Five subject positions were identified – The Pragmatic Woman (who constructs a practical positioning in learning how to survive in academia); The Prototypical Woman (expected to engage in their professional and personal responsibilities in feminine, maternal ways); The Credible Woman (the perception of what Australian public higher education setting ideally expects); The Super Woman (who balances her professional and personal lives, and puts the needs of the institution, and other people, before herself); and The Sacrificial Woman (sacrificing the self to meet the demands of other personal and professional responsibilities). The identified discourses created subjectivities for the middle-career women academics that emphasised the need for them to work even harder, as they were afforded less allowances, and held to higher standards, than their male academic counterparts. Highlights: Many personal and professional responsibilities interact for middle-career women academics. Burdens and pressures are placed on them through structural and institutional inequities. Middle-career women academics experiences form the context for constructing their identities. Middle-career women academics are afforded less allowances than their academic counterparts. Middle-career women academics are held to higher standards than their academic counterparts.